2002
DOI: 10.12968/bjom.2002.10.8.10592
|View full text |Cite
|
Sign up to set email alerts
|

Towards a social model of childbirth: part one

Abstract: Though critiques of the biomedical model of childbirth have served to highlight the shortcoming of present-day maternity services, writing on an alternative social model is less developed. Specifically, contrasting beliefs within each model and how that is applied requires more reflection. These two articles suggests how the social model of birth may be understood, both as beliefs and values and as an applied midwifery model. Part one examines contrasting emphases between a medical and social model in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Foucault (1977) argued that power relations function through medical surveillance, presented as expert knowledge, which when internalised by the patients and other health care professionals, resulted in acceptance of the medical position, however this position can be resisted if the subordinate individual or group are empowered. Walsh et al (2002) further contended that as long as midwives continue to be employed by the NHS, and are based in Consultant units, where birth continues to be managed using an obstetric model, change will continue to be slow. They argued that if midwives were all community based and more closely aligned with women and social care workers, the social model of care would be enabled to flourish (Walsh et al, 2002).…”
Section: Emergence Of Medicalisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Foucault (1977) argued that power relations function through medical surveillance, presented as expert knowledge, which when internalised by the patients and other health care professionals, resulted in acceptance of the medical position, however this position can be resisted if the subordinate individual or group are empowered. Walsh et al (2002) further contended that as long as midwives continue to be employed by the NHS, and are based in Consultant units, where birth continues to be managed using an obstetric model, change will continue to be slow. They argued that if midwives were all community based and more closely aligned with women and social care workers, the social model of care would be enabled to flourish (Walsh et al, 2002).…”
Section: Emergence Of Medicalisationmentioning
confidence: 99%
“…Walsh et al (2002) further contended that as long as midwives continue to be employed by the NHS, and are based in Consultant units, where birth continues to be managed using an obstetric model, change will continue to be slow. They argued that if midwives were all community based and more closely aligned with women and social care workers, the social model of care would be enabled to flourish (Walsh et al, 2002). Moreover, Fisher et al (2006) found that women experienced childbirth fear at both a personal and social level, which was exacerbated by the medicalised environment that birth takes place in.…”
Section: Emergence Of Medicalisationmentioning
confidence: 99%
See 3 more Smart Citations